1962
DOI: 10.1530/acta.0.0410351
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lynestrenol) on Animal Reproduction

Abstract: Lynestrenol is a potent oral pregestagen. The oral activities in the Clauberg and Corner & Allen tests are of the same order as that of subcutaneously administered progesterone. No effect was found in the tests for deciduomagenic activity in the mouse and for the maintenance of pregnancy in the rat. Lynestrenol has a marked inhibitory action on ovulation in the rat. This effect can be enhanced by low doses of oestrogen, which themselves are inactive in this respect. The main cause of this effect seems to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

1964
1964
1999
1999

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…It was not expected, however, that treatment with lynoestrenol, a dominant progestational steroid, would also result in reduction of uterine histamine. The weak oestrogenic activity reported for lynoestrenol (Overbeek, Madjerek & Divisser, 1962;Okada, Amatsu, Ishihara & Tokuda, 1964;Paulsen, 1965) has also been shown by the effect of this steroid on the vaginal smear (Abdel-Aziz et al, 1974) and the histological changes in the uterus observed in the present work. The reduction in uterine histamine observed after treatment with lynoestrenol might thus be mediated through its oestrogenic action or through its progesta¬ tional and oestrogenic actions.…”
supporting
confidence: 83%
“…It was not expected, however, that treatment with lynoestrenol, a dominant progestational steroid, would also result in reduction of uterine histamine. The weak oestrogenic activity reported for lynoestrenol (Overbeek, Madjerek & Divisser, 1962;Okada, Amatsu, Ishihara & Tokuda, 1964;Paulsen, 1965) has also been shown by the effect of this steroid on the vaginal smear (Abdel-Aziz et al, 1974) and the histological changes in the uterus observed in the present work. The reduction in uterine histamine observed after treatment with lynoestrenol might thus be mediated through its oestrogenic action or through its progesta¬ tional and oestrogenic actions.…”
supporting
confidence: 83%
“…By contrast, lynoestrenol, in the dose used, was shown to possess a weak oestrogenic activity in addition to a dominant progestational action. The weak oestrogenic activity of lynoestrenol has also been reported by several workers (Overbeek et al, 1962;Okada, Amatsu, Ishihara & Tokuda, 1964;Paulsen, 1965). It seems possible that the dominant progestational action of lynoestrenol is responsible for the failure of the appearance of excitatory a-adrenoceptors in the majority of rats treated with this steroid.…”
supporting
confidence: 61%
“…Vaginal smears were examined daily throughout the period of treatment. The dosage and duration of treatment ensured a maximal contraceptive effect (Goldzieher, Moses & Ellis, 1962;Overbeek, Madjerek & de Visser, 1962;Gardner, Gnoj, Watnick & Gibson, 1964).…”
mentioning
confidence: 99%
“…Furthermore, it should be mentioned that the effectiveness of oral administration of progestins and estrogens in contraceptive pills (33) may involve more than the inhibition of ovulation. Their effects on egg transport may be of importance whether or not the inhibition of nidation is concerned (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%